Rozwój kapitałowych filarów emerytalnych w Polsce - Trippner, Paweł (Development of Pension Capital Pillars in Poland, 2008)
The article introduces the current pension system in Poland. It underlines the necessity for investing in non-obligatory third pillar by future pensioners. The paper presents an analysis of level of interest in investing in third pension pillar by using Company Pension Plans or Individual Pension Accounts. The structure of this pillar has been analyzed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 436-443